Two New Species of Fabaceae From India - Hemadri, Koppula (Indian Forester, 1971)
Alysicarpu, vasavadae Hemadri sp. Nov. from Maharashtra, Madhya Pradesh and Mysore States and Smithia agharkarii Hemadri sp. nov. from Maharashtra are described and illustrated.